ER stress as a trigger of UPR and ER-phagy in cancer growth and spread - Cherubini, Alessandro; Zito, Ester (Frontiers in Oncology, 2022)
Tumors can survive environmental and metabolic stress by triggering homeostatic responses which re-establish the pre-stress status and permit them to grow and thrive. The endoplasmic reticulum is the organelle where proteins undergo post-translational modifications, are folded and exported to the secretory pathway. Its environment and activity are therefore fundamental for proteostasis, i.e. the plethora of mechanisms controlling protein formation, folding, degradation and secretion, needed to assure protein balance and cellular health. In different tumor-related conditions, such as after activation of oncogenes or under hypoxia and nutrient deprivation, ER experiences stress, triggered by a high load of proteins to be folded compared to the limited folding capacity of the organelle. As a consequence, three ER membrane receptors and the related unfolded protein response (UPR) are activated. UPR comprises a complex interconnection between signal transduction pathways which promote a homeostatic response that acts by increasing the protein chaperones and ER-associated protein degradation (ERAD) on one hand and attenuating protein translation on the other. ER-phagy, literally “eating” the ER, is part of another homeostatic response consisting of the clearance of non-functional ER portions including misfolded protein. This response is also activated by a set of dedicated ER-phagy receptors after ER stimuli, which overlap the stimuli generating ER stress. Thus, UPR and ER-phagy are two closely related homeostatic mechanisms that cooperate in re-establishing ER homeostasis. However, while the role of UPR in favoring cancer growth and thriving by promoting angiogenesis, metastasis, chemotherapy resistance, and epidermal-to- mesenchymal transition (EMT) is consolidated, that of ER-phagy is still in its infancy. This essay provides an overview of emerging concepts on ER stress, UPR, and ER-phagy and their crosstalk in tumorigenesis. We also critically review new findings on their pharmacological targeting in cancer.